Integrating Wordwall to Increase Student’s Enthusiasm in Learning English Vocabulary Achievement: A Study of Eighth Grade Students at UPT SMP Negeri 4 Panca Rijang - Nur Aini; Sam Hermansyah; Sitti Aisa; Nurul Faradillah (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study aimed to investigate the effectiveness of integrating Wordwall in enhancing students’ enthusiasm and English vocabulary achievement among eighth-grade students at UPT SMP Negeri 4 Panca Rijang. Vocabulary plays a fundamental role in language learning; however, many students experience low motivation and limited engagement due to conventional teaching methods. Therefore, the use of interactive digital media is considered a potential solution to address this issue. This research employed a quantitative approach with a quasi-experimental design involving two groups: an experimental group taught using Wordwall and a control group taught through conventional methods. The sample consisted of 45 students. Data were collected through a vocabulary achievement test (pre-test and post-test) and an observation rubric measuring students’ enthusiasm. The data were analyzed using descriptive and inferential statistics, including paired and independent sample t-tests. The findings revealed that students taught using Wordwall showed a significant improvement in both vocabulary achievement and learning enthusiasm compared to those taught using conventional methods. The experimental group demonstrated higher levels of active participation, motivation, and cognitive engagement during the learning process. The integration of Wordwall as a digital game-based learning medium is effective in improving students’ enthusiasm and vocabulary achievement. It is recommended that English teachers incorporate interactive digital tools such as Wordwall to create more engaging and meaningful learning experiences.